INTEGRATED MARKETING COMMUNICATIONS IN MARKETING PUBLIC RELATIONS PERSPECTIVE (Survey on TourismDestinationDevelopmentinThree Colorsof LakeKelimutu, Ende, East Nusa Tenggara Province) - NUNUNG RUSMIATI (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2014)
The tourism industry also affects a tourist-destination country in term of cross-culturalunderstanding. To support the tourism activity in a tourist destination, it is necessary to have agood destination marketing strategy. Destination Marketing is a communication process withpotential visitor to influence their tour destination. Destination Marketing possessed major rolein the process of implementation. It does so, by its effort to communication the value, vision andmission and it competes to promote tourism destination. The potential Indonesian tourismindustry will continue to suffer if the image of Indonesia, as a safe and comfortable country, isnot correctly conveyed with the right strategy. It is time for the government to develop,communicate and promote tourism destination in other parts of Indonesia, especially in easternparts of Indonesia. The research questions of this case study of integrated marketingcommunications from the perspective of public relations regarding potential tourist destinationin one of eastern parts of Indonesia: Lake Tiga Warna Kelimutu, the Residence of Ende, theProvince of Nusa Tenggara Timur are: Is there any effect of word of mouth communication onthe attractiveness of tourist destination?, Is there any effect of marketing public relation on theattractiveness of tourist destination?, Is there any effect of destination marketing management onthe attractiveness of tourist destination? , Is there any effect of Integrated MarketingCommunication (IMC) on the attractiveness of tourist destination?, Is there any effect ofmarketing public relations (MPR) on the attractiveness of tourist destination?, Is there anyeffect of Integrated Marketing Communication (IMC) on destination marketing management?, Isthere any effect of tourism infrastructure on the attractiveness of tourist destination?, Is thereany effect of supporting tourism industry on the attractiveness of tourist destination?, Is thereany effect of the attractiveness of tourist destination on customer satisfaction?, and Is there anyeffect of customer satisfaction on behavior intention?